The The Kinetics of Carbon and Nitrogen Mineralization of Different Organic Amendments in the Soil - IBIJBIJEN, Jamal; EL GHAZOUANI, Ouiam; BOUAMRI, Rachid (European Journal of Applied Sciences, 2022)
The exploitation of exogenous organic matter from fresh or composted livestock manure in agriculture is an effective source that addresses the problem of soil depletion and provides essential nutrients to plants. It can also cause worry about environmental degradation, such as CO2 emissions and nitrate leaching. The rational use of these organic soil amendments requires additional research, which still remains limited in terms of articles and books in Morocco. The objective of our research is to study the kinetics of carbon and nitrogen mineralization of the different organic amendments, sheep manure (SM), cattle manure with straw (CM), two composts (CA, CF), and poultry manure laying hen (PL), by an incubation method under controlled laboratory conditions, and characterize the organic matter (OM) by biochemical fractionation. In the light of these results obtained, it can be seen that laying hen droppings induced the highest level of carbon and nitrogen mineralization, followed by sheep manure and cattle manure with straw which recorded an intermediate rate of carbon mineralization. And high nitrogen immobilization, these two materials are considered to be a transition point between the manure and the two compost, which recorded slow and low carbon and nitrogen mineralization. Statistical analysis endorsed a correlation between the kinetics of carbon mineralization and biochemical fractionations of organic matter in EOMs.